2022
DOI: 10.1177/23259671221094346
|View full text |Cite
|
Sign up to set email alerts
|

Extreme Hinge Axis Positions Are Necessary to Achieve Posterior Tibial Slope Reduction With Small Coronal-Plane Corrections in Medial Opening Wedge High Tibial Osteotomy

Abstract: Background: Both coronal- and sagittal-plane knee malalignment can increase the risk of ligamentous injuries and the progression of degenerative joint disease. High tibial osteotomy can achieve multiplanar correction, but determining the precise hinge axis position for osteotomy is technically challenging. Purpose: To create computed tomography (CT)–based patient-specific models to identify the ideal hinge axis position angle and the amount of maximum opening in medial opening wedge high tibial osteotomy (MOWH… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 37 publications
2
5
0
Order By: Relevance
“…At the same time, according to the findings of this study, changes of hinge rotation between 20° and 90° had little influence on the MPTA, which was mainly influenced by the opening height of the osteotomy gap. These findings were also observed by Eliasberg et al [ 8 ]. Based on the results of this study, we proposed a formula (PTS = 19.39 + 0.97 × hinge rotation + 0.61 × gap height ) to predict the aspired changes in the coronal and sagittal plane, with regard to the factors opening height and hinge rotation.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…At the same time, according to the findings of this study, changes of hinge rotation between 20° and 90° had little influence on the MPTA, which was mainly influenced by the opening height of the osteotomy gap. These findings were also observed by Eliasberg et al [ 8 ]. Based on the results of this study, we proposed a formula (PTS = 19.39 + 0.97 × hinge rotation + 0.61 × gap height ) to predict the aspired changes in the coronal and sagittal plane, with regard to the factors opening height and hinge rotation.…”
Section: Discussionsupporting
confidence: 87%
“…Although not clinically visible, this posterior hinge malrotation was associated with a significant increase of the PTS by an average of 3.3° [ 15 ]. In a computational simulation model, Eliasberg et al picked up on these findings and proposed a hinge axis rotation of 102.6° relative to the posterior condylar axis, in order to achieve a PTS‐neutral coronal correction during mowHTO [ 8 ]. This observation may be explained by a compensational effect, with regard to the tibial anatomy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results show a clear (and expected) coupling between the orientation of the HA in 3D space and its effect on alignment parameter values in all 3 anatomical reference planes. Although similar effects of HA orientation on alignment in 2 of the 3 anatomical reference planes as the ones reported in the present study have been reported before, 18 , 19 , 20 , 22 , 23 , 37 Jörgens et al. 31 investigated the effects of HA rotation and HA tilt on alignment angles in all 3 anatomical reference planes.…”
Section: Discussionsupporting
confidence: 87%